Influência da configuração do preparo cavitário na resistência à fratura e adaptação marginal de restaurações indiretas em cerômero - Fonseca, Rodrigo Borges (2004)
The aim of this study was to evaluate the influence of cavity preparation design on marginal adaptation and fracture resistance of indirect ceromer restorations. Ninety human mandibular molars with similar dimensions were divided into 9 groups. The teeth roots were embedded in a polystyrene resin reproducing the periodontal ligament. The control group had only intact teeth and the other teeth received the following cavity preparations: 2) conservative inlay; 3) extensive inlay; 4) conservative oclusal isthmus onlay with mesio-buccal cusp coverage; 5) extensive oclusal isthmus onlay with mesio-buccal cusp coverage; 6) conservative onlay with buccal cusps coverage; 7) extensive onlay with buccal cusps coverage; 8) conservative overlay; 9) extensive overlay. Prepared teeth were restored with a ceromer material, Targis (Ivoclar-Vivadent). Silicon impressions of prepared teeth were taken; the indirect restorations were manufactured and then adhesively fixed on each tooth. The teeth were submitted to an ultimate compressive strength test on a universal testing machine, EMIC DL-2000, at a crosshead speed of 0,5mm/min. The modes of fractures were classified according to four levels of tooth final damage. Data were submitted to statistical analysis by ANOVA (α=0,05) following Tukey test (95% confidence intervals) or Fisher LSD test (99% confidence intervals), and Pearson correlation coefficient. Fracture resistance results failed to show differences among all groups of prepared teeth, but showed difference between prepared teeth and control group (P=0,000). Two-way ANOVA also failed to show any particular difference when considering the oclusal isthmus width alone (P=0,980) or cuspal coverage (P=0,273), or even the interaction between these factors (P=0,972). A great number of teeth had a harmful mode of fracture, which extended till the biological width. Marginal adaptation results showed differences among the prepared teeth (P=0,005). G3 showed the best marginal adaptation and G2 the worst one. Two-way ANOVA showed particular differences when considering the oclusal isthmus width alone (P=0,001): in general, extensive oclusal isthmus preparations presented better results than conservative ones; however, the test failed to show differences when considering the cuspal coverage (P=0,425) or the interaction between both factors (P=0,301). Pearson correlation coefficient showed significance only on G7. The absence of differences on fracture resistance among prepared teeth and their fracture modes clear show the adhesive capacity of this restorative treatment; thus it seems not to be necessary cuspal coverage when tooth preparations are similar to the ones of this study. Best marginal adaptation of extensive oclusal isthmus preparations over conservative ones seems to be related to the reduced necessity of internal restoration adjustment.